Rumination and “hot” executive function of middle school students during the COVID-19 pandemic: A moderated mediation model of depression and mindfulness - Li, Ying; Qu, Guiping; Kong, Huiyan; Ma, Xiaobo; Cao, Lei; Li, Tiantian; Wang, Yue (Frontiers in Psychiatry, 2022)
Background The outbreak of COVID-19 had a widely negative effect on adolescents’ academics, stress, and mental health. At a critical period of cortical development, adolescents’ cognition levels are highly developed, while the ability of emotion control is not developed at the same pace. Faced with negative emotions such as stress and social loneliness caused by COVID-19, adolescents’ “hot” executive function encounters severer emotional regulation challenges than ever before. Objective The present study established a moderated mediation model to investigate the impact of rumination on “hot” execution function among Chinese middle school students during the COVID-19 pandemic, and the specific role of depression and mindfulness in the association. Materials and methods This cross-sectional study was conducted on 650 students recruited from a province in central China. The participants completed questionnaires and experiment between July 2021 and August 2021. Rumination Responses Scales, Self-rating Depression Scale, and Mindful Attention Awareness Scale were used to measure the level of rumination, depression, and mindfulness. The reaction time and accuracy of the emotional conflict experiment were recorded to reflect the “hot” executive function. Results The results of the moderated mediation model indicated that rumination of middle school students significantly and positively predicted depression in adolescents (β = 0.26, p < 0.001). Meanwhile, the indirect effect of depression on the relationship between rumination and “hot” executive function was significant; depression partially mediated this relationship (word-face congruent condition: β = −0.09, p < 0.01; word-face incongruent condition: β = −0.07, p < 0.05). Furthermore, mindfulness buffered the association between rumination and depression, according to moderated mediation analysis (β = −0.11, p < 0.001). For adolescents with low levels of mindfulness, the relationship was substantially stronger. Conclusion In the context of the COVID-19 pandemic, middle school students’ rumination would lead to depression, which can negatively impact their “hot” executive function. Besides, mindfulness could resist the adverse effect of rumination on depression. The educators should pay more attention to students’ mental health, provide targeted strategies that boost mindfulness to promote their cognitive flexibility, and thus protect the normal development of their executive function during crisis events.